2019
DOI: 10.2174/1389202920666190326145459
|View full text |Cite
|
Sign up to set email alerts
|

Identification of tRNA-Derived Fragments Expression Profile in Breast Cancer Tissues

Abstract: Background: In recent years, tRFs(transfer RNA-Derived Fragments) and transfer RNADerived Stress-induced RNAs (or tRNA halves) have been shown to have vital roles in cancer biology. We aimed to reveal the expression profile of tRNA-derived fragments in breast cancer tissues in the study, and to explore their potential as biomarkers of breast cancer. Methods: We characterized the tRNA-derived fragments expression profile from 6 paired clinical breast cancer tissues and adjacent normal samples. Then we select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 37 publications
0
30
0
Order By: Relevance
“…tsRNA-26576 upregulation induced migration while suppressing the cellular apoptosis, and served as a potential target therapy and also a predictive marker [43]. In another research, down-regulation of tRF-32-Q99P9P9NH57SJ and tRF-17-79MP9PP were indicated as well as up regulation of tRF-32-XSXMSL73VL4YK [44]. Using high-throughput sequencing, circulating tDR-7816 was predicted as an oncogene effect on xenobiotic metabolic processes in early non-TNBC breast cancer.…”
Section: Breast Cancermentioning
confidence: 97%
“…tsRNA-26576 upregulation induced migration while suppressing the cellular apoptosis, and served as a potential target therapy and also a predictive marker [43]. In another research, down-regulation of tRF-32-Q99P9P9NH57SJ and tRF-17-79MP9PP were indicated as well as up regulation of tRF-32-XSXMSL73VL4YK [44]. Using high-throughput sequencing, circulating tDR-7816 was predicted as an oncogene effect on xenobiotic metabolic processes in early non-TNBC breast cancer.…”
Section: Breast Cancermentioning
confidence: 97%
“…They are expressed and dysregulated in various cancers [58] (Table 1). The heterogeneity and stability of tRFs make it suitable biomarkers for cancer diagnosis and prognosis [19]. Acquired treatment resistance is the main dilemma of cancer treatment [59].…”
Section: Classification Of Trfs and Tirnas And Their Roles In Cancersmentioning
confidence: 99%
“…5′-tiRNA Val tiRNA-5 5′-tiRNAVal overexpression significantly suppresses breast tumor cell proliferation, migration and invasion. [18] tRF-32-Q99P9P9NH57SJ tiRNA-5 tumour stage and lymph node metastasis [19] SHOT-RNAAsp-GUC SHOT-RNAHis-GUG SHOT-RNALys-CUU tiRNA SHOT-RNAs enhance cell proliferation. [20] tDR-000620 tRF aggressive phenotype of breast cancer stem cells [21] 5′-tiRNA Asp , 5′-tiRNA His tiRNA-5 elevate in breast cancer [22] tRF tRF Leu − CAG tiRNA-5 Promote cell proliferation and G0/G1 cell cycle progression [27] pancreatic cancer AS-tDR-000064 AS-tDR-000069 AS-tDR-000102 AS-tDR-001391 tiRNA-5 diagnostic and therapeutic biomarkers [28] colorectal cancer tRF/miR-1280 tRNALeu and pre-miRNA suppress colorectal cancer growth and metastasis [29] tiRNA-Tyr-GTA tiRNA-5 Targets of tiRNA-Tyr-GTA are mainly enriched in the PPAR signaling pathway.…”
Section: Mechanisms Of Breast Cancer Resistance Related To Trfs and Tmentioning
confidence: 99%
See 1 more Smart Citation
“…tRNA-derived RNA fragments (tRFs) are sncRNAs that are derived from the 5′ or 3′ end of mature or precursor tRNAs [ 12 ]. Recent advances in sequencing technology have facilitated the determination of the expression profiles of tRFs in various cancers, including breast, colon, pancreatic, and prostate cancers [ 13 , 14 , 15 ]. Compared to other studies that have reported the tRF profiles of other carcinomas, studies on prostate cancer have progressed from the determination of tRF expression profiles to the use of tRFs therapeutically or diagnostically [ 12 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%